Effectiveness of Toolbox Talks as a Workplace Safety Intervention in the United States: A Scoping Review - Gregory D. Kearney; Jamie Hisel; John A. Staley (Safety, 2025)
Toolbox Talks are widely adopted and valued by supervisors and safety managers as a core component of occupational safety and health training, yet their effectiveness as an intervention has not been systematically evaluated in the peer-reviewed literature. Persistently high rates of occupational fatalities and injuries, particularly among high-risk industries, compounded by an increasingly diverse workforce, involving linguistic diversity, high turnover, and mobile job sites, highlight the urgent need for evidence-based approaches to safety training. This scoping review addresses this gap by examining the effectiveness of Toolbox Talks as an occupational safety intervention through three guiding questions focused on their reported impact, implementation challenges, and the best practices and delivery methods that enhance their effectiveness. The Adult Learning Theory served as the framework to assess evidence-based studies. Four bibliographic databases were used to search for studies published between 2000 and 2024. Data were charted based on effectiveness, measured as outcomes, and categorized as any combination of safety knowledge, attitudes, beliefs, behavior, or health outcomes. Unforeseen challenges and recommended best practices were gleaned from each study to provide additional insight. A total of fourteen (14) studies met our inclusion criteria, with the majority centered on construction workplaces (n = 10). Reported effectiveness outcome measures were positive across all studies, with notable improvements in workers’ safety knowledge. Training challenges encountered included worker disengagement, language diversity, and production pressures. Recommended best practices for increasing Toolbox Talk training effectiveness included conducting regularly scheduled training, engaging workers, training supervisors, and providing culturally appropriate and tailored materials. While Toolbox Talks demonstrate significant potential to enhance workplace safety, their effectiveness is hinged on the quality of content and delivery methods, particularly when aligned with adult learning principles that emphasize relevance, engagement, and experimental learning. Future research should explore how emerging technologies, such as e-learning platforms, combined with cultural inclusive approaches and long-term impact assessments, can optimize the design and implementation of Toolbox Talks across diverse occupational settings.